EVALUASI PENANGGULANGAN KERUSAKAN STRUKTUR - SUHARA
It is a common problem that buildings which are constructed on soft soil will tend to settle if the effective stress at the building areas increase. The difference of loading intensity on each foundation will cause differential settlement. This study is intended to investigate the stability of an existing building which has a differential settlement problem. The Factory Building of Flour Mills in Semarang, Central Java is taken as a sample for this study. The site monitoring data of settlement on each foundation will be used to estimate the total settlement on each foundation at the end of consolidation process. This calculation result will be used as input to determine the spring constant of the foundations. Using these spring constants as input, the building structures will be analyzed using a Static Finite Element Program to determine the failure pattern of the structures during settlement process. This failure pattern will be used to determine the strengthening method of the structure. On this case study, the strengthening of the structure will use infill wall and combine it with external prestressing.